Adaptation as a reason for the Neolithization? Case study from the present day Croatia - Šošić Klindžić, Rajna (2011)
In the Northern Balkan, the first wave of Neolithisation stopped somewhere in the Middle of the Great Hungarian Plain and to the West around 100 km to the east from the present day Zagreb. The Northern border is called “ecological barrier” in the archaeological literature, and the same model can be applied to the western border where there are much less data The research of influence of the various aspects of the environment on the past cultures is important not only to get answers to scientific questions but in order to try to explain to the broader community the complexity and diversities of different cultures and cultural processes. This example shows common culture- nature dichotomy in explaining dynamics and reasons for cultural change in prehistoric times.
Projekt MZOS
ENG